EVALUATION OF ANTIBACTERIAL ACTIVITY 5-AMINO-3-METHYLISOXAZOLE-4-CARBOHYDRAZIDE AND 5-AMINOISOXAZOLE[5,4-d]PYRIMIDIN-4-ONE DERIVATIVES - Marcin Mączyński; Andrzej Regiec; Paulina Płoszaj; Miroslawa Kacaniova; Agnieszka Piwowar (Polskie Towarzystwo Farmaceutyczne, 2023)
Searching for new compounds with specific biological activity in relation to various bacterial strains due to the increasing number of bacterial infections and the frequently developing antimicrobial resistance (AMR) is a significant problem in healthcare. Based on previous promising research related to the activity of isoxazole-4-carbohydrazide derivatives, we currently examined different substituted isoxazole-4-carbohydrazide derivatives in vitro against a panel of bacterial strains. In this work we evaluated antibacterial activity of 30 derivatives, previously described as mildly antimycobacterial, in 10 bacterial strains (5 Gram-negative (G-) and Gram-postive (G+) bacterias). Based on minimum inhibitory concentration (MIC), the mainly MIC50 and MIC90 values, the tested derivatives generally have shown rather weak and mild antibacterial activity. The most active compounds were 3d and 4d, both with methyl substituent in benzene ring. More detailed examination should be continued but this research increased the library of isoxazole derivatives with broad biological activity.